Antimicrobial and Antioxidant Activity of Apricot (Mimusopsis comersonii) Phenolic-Rich Extract and Its Application as an Edible Coating for Fresh-Cut Vegetable Preservation. (21st October 2022) - Lima, Emília Maria França; Matsumura, Caroline Harumi Silva; da Silva, Geovana Luísa; Patrocínio, Isabela Cristina Soares; Santos, Catarina Angeli; Pereira, Patrícia Aparecida Pimenta; Hassimotto, Neuza Mariko Aymoto; Pinto, Uelinton Manoel; da Cunha, Luciana Rodrigues
Abstract : Edible coatings have several advantages in preserving foods, such as avoiding water loss, controlling microbial growth, and reducing the need for preservatives added directly to the product. Antimicrobial action can be obtained by adding antimicrobial substances including phenolic compounds commonly found in plant extracts. This study evaluated the phenolic compounds content, antioxidant and antimicrobial activity of pulp, and seed extracts of Mimusopsis comersonii (popularly known in Brazil as abrico ), besides the phenolic compounds were identified and quantified in the pulp extract. Edible coatings were incorporated with pulp extract in order to evaluate the preservation of minimally processed apples and baroa potatoes against foodborne bacteria, and enzymatic browning was also determined. Myricetin-3-glucoside, quercetin-3-glucoside, and kaempferol-3-glucoside were identified as major flavonoids in the apricot pulp extract. The seed and pulp extracts inhibited all tested microorganisms, especially Staphylococcus aureus and Salmonella Typhimurium. Edible coatings added with 9% of phenolic extract showed in vitro antimicrobial activity, in addition to being effective in preventing enzymatic browning in minimally processed apples and baroa potatoes for up to 15 days of storage. They were also effective in reducing up to 2 log CFU/g of aerobic mesophiles after 15 days of storage for apples, even though no microbial inhibition in baroa potatoes was observed under the same conditions. The addition of pulp phenolic extract in edible coatings proved to be an alternative in the preservation of apples and in the antibrowning activity of minimally processed baroa potatoes.